Taṭbīq Ṭarīqah at-Ta`allum at-Ta`āwunī Bi Uslūb JIGSAW Li Tarqiyah Qudrah aṭ-Ṭalabah `Alā Fahm an-Nuṣūṣ al-`Arabiyyah (Dirāsah Ijrāiyyah Bi Ma`had SMPIT Madrasah al-Qurān Aceh Besar): (Aceh Besar مدرسة القرآن SMPIT لترقية قدرة الطلبة على فهم النصوص العربية (دراسة إجرائية بمعهد JIGSAW تطبيق طريقة التعلم التعاوني بأسلوب - Aulia Agustiar; Nur Chalis (The Department of Arabic Language Education, Pascasarjana Universitas Islam Negeri Banda Aceh of UIN Ar-Raniry Banda Aceh, Aceh, Indonesia., 2020)
Students at SMPIT Madrasatul Quran boarding school memorize verses of al-Quran, memorize Arabic vocabulary, learn Arabic grammar, and learn Arabic texts. This process will be a good attempt to improve students' ability to read and understand Arabic texts. In reality, however, some students are not able to read and understand Arabic texts well, as there are errors in